Current Trends in Operative Treatment of Scaphotrapeziotrapezoid Osteoarthritis: A Survey among European Hand Surgeons - Berkhout, Merel J.-L.; Yin, Qiqi; Ritt, Marco J. P. F. (Journal of Wrist Surgery, 2020)
Objective Based on the available evidence, the optimal surgical treatment for isolated scaphotrapeziotrapezoid oarthritis (STT OA) remains unclear. The purpose of this study is to explore the prevailing surgical practice for isolated STT OA among European hand surgeons. We hypothesized that a considerable variance exists in the current surgical practice among hand surgeons in Europe.Methods An online survey was distributed to 20 participating member states of the Federation of European Societies for Surgery of the Hand (FESSH). Respondents were questioned on their country of practice, surgical experience, preferred surgical procedure, frequency of performing this procedure, factors in decision-making, and other performed surgical procedures.Results Four hundred and sixty-five responses were received with an estimated response rate of 19%. Trapeziectomy with partial trapezoidal excision was the surgical treatment of choice among the participating hand surgeons in Europe (38%), followed by STT joint fusion (30%), and distal scaphoid excision (14%).Conclusion This survey provides an insight into the surgical management of isolated STT OA among hand surgeons in Europe. A wide variety of preferred treatment techniques were found. Evidence concerning the optimal surgical treatment has not been established. Future prospective randomized studies comparing different techniques are warranted.
Keywords: scaphotrapeziotrapezoid; STT osteoarthritis; wrist; survey